The helplessness of the leading role childhood at the fiftieth anniversary of Neira Vilas’ Memorias dun neno labrego publication. From The Little Match-Seller to Balbino - Caveiro, Laura; González Vázquez, Mercedes (Madrygal. Revista de Estudios Gallegos, 2011)
In this article we will try to make an approach to the child´s helplessness of the leading role childhood through the figure of Balbino. Acontroversy that was the reason of a social criticism in Castelao´s literature. It starts up as a pre-assumption of the maximum expression of helplessness that symbolises “The Little Match-Seller” by Hans Christian Andersen. Several convergences and divergences arise in the rating of this situation for the main child´s characters. The fiftieth anniversary of the first edition of Memorias dun neno labrego, where Neira Vilas portrayed the peculiar features of the child´s helplessness in the postwar period of the rural Galicia, is commemorated in the 2011.
Keywords: Helplessness; leading role childhood; fiftieth anniversary; Memorias dun neno labrego; Neira Vilas; The Little Match-Seller; Balbino.